A municipalização das escolas rurais de Pires do Rio - GO (1980 - 2008) - Pego, Douglas Souza (2023)
Our initial interest was to explore the culture of schools in the 1980s in Pires do Rio (GO), however, the rural aspect is highlighted as part of the culture of that population. Rural schools therefore became the subject of this study. The research aims to contribute to the understanding of rural education in Brazil, especially after 1980. The authors suspect that rural schools in Pires do Rio (GO) played a role in overcoming illiteracy in the region. The text outlines the four parts of the research, which include a brief presentation of the history of education in Brazil, an analysis of education in Goiás from 1969 to 1980, the historical context of Pires do Rio and, finally, the municipalization of rural schools in the municipality. The research is classified as mixed, combining qualitative and quantitative approaches. Data was collected mainly through documentary analysis, using sources such as Municipal Laws, Draft Laws, Municipal Education Council Opinions, Minutes, and other documents related to rural schools. The authors recognize the importance of experiences and memories in formal and school education. Thus, the research aims not only to understand the municipalization process, but also to highlight the educational experiences, challenges and opportunities in rural communities. The text highlights the relevance of the study of school institutions in the History and Historiography of Education, highlighting advances in debates and events since the 1990s. The bibliographical approach is mentioned as fundamental to covering a wide range of historical phenomena. The research methodology involves a mixed qualitative and quantitative approach, using documentary analysis as the main method of data collection. Finally, the authors recognize the need for site visits, interviews and contact with school materials to complement the research, especially to fill in gaps about pedagogical practices in rural schools. The text concludes by highlighting the continued importance of the research, acknowledging the incompleteness of some points and indicating the intention to continue investigating the process of municipalization of rural schools in Pires do Rio. The authors hope that the study will contribute to understanding the history of rural education in the municipality of Pires do Rio (GO).